Decolonizing campus spaces to include mixed‐race Indigenous students. Issue 174 (5th November 2021) - Bazemore‐James, Cori; Boyd, Beth
Abstract: This article delves into the uniquely layered barriers faced by mixed‐race Indigenous college students in campus environments. Observations are provided on how to decolonize our practices to better support their identity development and inclusion.